Digital Transformation in Micro, Small, and Medium Enterprises: Opportunities and Challenges in Cak Pendi’s Madura Satay Business, Sungelebak Village - Hartini, Mawaddah Yuli; Rohman, Abdur (ITQAN: Journal of Islamic Economics, Management, and Finance, 2025)
This study discusses the digitalization of Micro, Small, and Medium Enterprises (MSMEs) through a case study of Warung Sate Madura Cak Pendi in Sungelebak Village. The purpose of the study is to identify opportunities and challenges of digitalization in the context of traditional MSMEs. This study uses a qualitative approach. Data were collected through in-depth interviews with business owners and customers, as well as related literature studies. The results show that digitalization offers significant opportunities, including increased market access and operational efficiency through social media and delivery services. However, challenges arise from intense competition, the need to adapt to new technologies, and the requirement to maintain a traditional identity. Ethical digital strategies that align with Islamic values have proven to be crucial for fostering sustainable growth. The implications of this study emphasize the importance of digital training and a value-based approach in supporting the transformation of MSMEs to remain competitive in the digital economy era.